Firebug eaudiobook - McBride, Lish (Firebug, 2014)
"Lish McBride's world of inventive dark magic and fantastic beings is not to be missed. By anyone. I'm telling you people, there are were-hares, a girl who flicks fire from her fingertips, and a were-fox with bouncy black feet (and an even cuter human body). If you want more than that, you want too much. Lish rocks."- Kendare Blake, author of Anna Dressed in Blood and Antigoddess "FIREBUG has it all-power-hungry villains, cool magic powers, foxy boys, and even vicious were-bunnies, all fueled by Lish McBride's signature non-stop wit. I love every moment spent in this oft-quirky, always spellbinding world, and can't wait to see what trouble Ava, Lock, and Ezra land themselves in next!"- Marissa Meyer, New York Times bestselling author of The Lunar Chronicles